Three years hence a father will four times as old as his son will be. Before two years he was seven times as old as his son was. Find their present ages.

Guest Feb 9, 2020

#1**+1 **

F= father's age NOW

S = son's age NOW

F+3 = 4( S+3) ( Three years hence a father will four times as old as his son will be.)

F-2 = 7(S-2) (Before two years he was seven times as old as his son was.)

two equations F+3 = 4S+12 and

F-2= 7S-14 solve for either F or S Multiply second equation by -1

-F + 2 = -7S + 14 add this to first eqaution

5 = -3S +26

-21 = -3S you should be able to take it from here.......

ElectricPavlov Feb 9, 2020